Pengaruh Kemampuan, Motivasi dan Semangat Kerja Terhadap Kinerja Karyawan di Bank BSI Kantor Cabang Suniaraja Bandung - Rida Sifa Isatun Rodiah; Yudhy Yudhy; Ade Iskandar Nasution (Jurnal Dimamu, 2022)
This research was motivated by the lack of ability, motivation and enthusiasm for work carried out at Bank BSI KC Suniaraja Bandung. to find out how the influence of ability, motivation and morale on employee performance at Bank BSI Suniaraja Bandung partially and simultaneously. The object of this research is the employees at Bank BSI KC Suniaraja Bandung. This type of research is quantitative associative, primary data collection techniques by conducting observations, interviews, questionnaires and literature study. The population is 32 respondents. The collection of samples using the saturated sample method. The results showed that there was an influence between ability on employee performance, namely 36.0% or tcount > ttable value (4.111>2.042). There is no influence between motivation on employee performance that is equal to 9.3% or tcount < ttable value (1.755 < 2.042). There is an influence between work morale on employee performance by 25.9% or tcount > ttable value (3,236. > 2,042). and there is a simultaneous influence of ability, motivation and work spirit on employee performance at Bank BSI KC Suniaraja Bandung as much as 39.8% or Fcount > Ftable value (6,170 > 2.95).